A mouth full of blood – autohaemorrhaging in three Ecuadorian snakes (Squamata: Colubridae & Tropidophiidae) - Rödel M.-O.; Loaiza-Lange A.; Penner J.; Neira-Salamea K.D.; Salazar Valenzuela, David (My University, 2023)
[No abstract available]
Keywords: acquired brain injury; Aphasia; case study; neuropsychology